Developing River Tourism on the Petagas River, Sabah: Understanding Community Perceptions and Potential Level of Engagement - Fiffy Hanisdah Saikim, Fiffy Hanisdah Saikim; Ing Grace Phang, Ing Grace Phang; Marry Tracy Pawan, Marry Tracy Pawan; Bruce Prideaux, Bruce Prideaux (Global business and finance review, 2024)
Purpose: The purpose of this study was to investigate the perceptions of local residents regarding the development of river tourism on the Petagas River in Kota Kinabalu, Sabah, Malaysia. Design/methodology/approach: Face-to-face semi-structured interviews were undertaken with 79 residents of river communities to explore their perceptions of river tourism development on the Petagas River, assess their views on their likely participation in river tourism, and identify problems they thought might inhibit tourism development. The conceptual framework was based on stakeholder theory to identify the interests and concerns of various stakeholders, and social exchange theory to identify the anticipated benefits if tourism development proceeded. Findings: The results show that while respondents were generally supportive of tourism development, they did recognize the need for river ecosystem restoration and the necessity to change many of their current practices and interactions with the river to ensure sustainable tourism growth. Research limitations/implications: The limitations of the study include the fact that it only looked at the settlements that were located along the Petagas River, bypassing the villages that were located nearby. The dependence on semi-structured interviews may limit the depth and breadth of the data collected from the study. In order to improve the validity of future research, it is recommended to utilise mixed-methods methodologies. Furthermore, a more thorough examination is required to assess the extent of community involvement, identify the specific training requirements, and devise efficient approaches for the restoration of the river ecology. It is essential to address these restrictions in order to develop tourist policies that are equitable and sustainable, with a focus on giving environmental protection and community engagement the highest priority. Originality/value: This study provides multiple contributions to the existing body of knowledge on river tourism. The findings utilise social exchange theory to highlight the significant significance that the potential for mutually advantageous interactions between communities and tourists can have in garnering local community support for tourism endeavours. Furthermore, the research also provides evidence for the importance of stakeholder theory as a crucial instrument in guaranteeing community involvement in the advancement of tourism.